La regulación legal y los principales términos económicos en los contratos de préstamo modernos - Piazza Risi, Walter (2017)
In the following article, the author starts marking differences between mutual and commodate contracts, action needed to adequately explain the negotiated economic terms in modern contracts. Indicated clauses whose function is to be important economic terms that are negotiated for the signing of structured loan contracts. It also mentions how the imputation of the payments of the borrower works, the use of the funds and the advance payment of the loan.